The Effect of Two Types of Ebbinghaus Visual Illusion on Learning a Motor Skill in Children with Autism Spectrum Disorder - Mohammad Hossein Zamani; Hamidreza Taheri Torbati; Aireza Saberi Kakhki; Majid Ghoshoni (University of Tehran, 2021)
The purpose of this study was to investigate the effect of visual illusion on the learning of throwing skills in autism children. The research method was semi-experimental with repeated design and retention test. The statistical sample of this study was 33 children of 10 years old who were selected available and were divided into three groups randomly: larger circle perceptions, smaller circle perceptions and control group. The tool used in this study was the Ebbinghaus illusion displayed on the ground and the beanbags for throwing from down to shoulder to goal. At first, the participants performed ten trials at the pre-test phase. Then, in the acquisition phase, 20 blocks completed 10 trials. 48 hours after the last session of the acquisition, a retention test was performed in 10 trials of the participant. To analyze the data, mixed analysis of variance analysis with repeated measures, one way analysis of variance and Tukey's follow-up were used. The results of this study showed that there was a significant difference between the groups both in the acquisition phase and in the retention phase between the groups, which this difference was in favor of the larger circle's perception group. Overall, the results of this study showed that a simple perceptual manipulation can increase motor learning in children with autism. Therefore, it is suggested to educators and sports practitioners to use this variable to improve their performance and improve their training sessions.